Program design and planning strategies in the delivery of culturally competent health and mental health prevention and treatment services to latino communities - Colon, Edgar (Journal of Multicultural Social Work, 1997)
It is important that the delivery of health and mental health prevention and treatment services within Latino communities be culturally sensitive. This article outlines several ways in which agencies can develop programs that can meet the needs of Latino communities. The most important aspect of the provision of health prevention and treatment services is that the organization integrates itself into the community through outreach, recruitment, and inclusion in decision-making. In addition, the organization needs to be structured so communication and participation from the community and health professionals are open and mixed. Otherwise, the likelihood of success of the provision of services in the community will be diminished. © 1996 Taylor & Francis Group, LLC.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/029-747-055-276-900 tex.type: [object Object]
Keywords: dept.swk